Člověk a "zvíře", které není jeho protikladem: od dekonstrukce k etice biocentrismu - Fišerová, Michaela (Filosoﬁcký časopis)
The paper invites us to revise the anthropocentric foundation of the philosophic distinction that is made between the concepts of human and animal. Following Derrida’s deconstruction, the author uncovers the systematic philosophic degradation of animals that helped to build modern humanism: human beings gave themselves the right to master non-human beings by comparing animal to man and defining it as an unequal, subordinated, and inferior being. The author suggests taking the concept of animal out of such an asymmetrically constructed binary opposition. By revising “animal” idioms burdened by the anthropocentric prejudice of human sovereignty, the author calls for a biocentric ethical position of interspecies mutuality. Firstly, she questions metaphysical presuppositions that make the philosophic conception of symbiosis between human and nonhuman beings impossible. Secondly, she suggests a philosophic solution, which opens inventive ways for an ethical approach to animals, both by means of a focus on nonverbal communication and by offering new idioms related to biocentric images of animality.